Evaluación del periodo de toxicidad de insecticidas usados para controlar gorgojos en arroz almacenado, en la provincia de Moyobamba - Pereira Panduro, Jhens Richer (2010)
At world, national and regional level, big difficulties exist for the control of plagues in stored foods, the most frequent and efficient method is the use of toxic in diverse important grains for the human feeding. Presently work of thesis titled Evaluation of the Period of Toxicity of Used Insecticides to Control Gorgojos in Stored Rice, in the County of Moyobamba". The central aspect of the investigation consists on determining the critical period of toxicity of some insecticides used in the control of rice stored in the County of Moyobamba and the ignorance of the time of duration of the agrotóxicos used in the conservation of the nutritious products with the purpose of avoiding the damages caused by the plagues like the "Gorgojos" (Sitophillus spp) that is a danger for the consumption of the local, regional, national and world residents, for such a reason the use of toxic in the storage of grains should be with the biggest cautions, following the precise indications and considering the necessary time of duration for the degradation of the poison used to combat to the plagues in the stored products, considering this innocuous way for the you consume. The present work one carries out in the National University of San Martin - Tarapoto, Ability of Ecology district of Moyobamba, county of Moyobamba and Department of San Martin. 05 treatments were determined for that which we put in recipients of plastics for this samples T1: Witness, T2: MALATHIÓN, T3: CARBARYL, SEVIN, T4: PHOSTEK and T5: Cipermetrina; in which it is necessary to emphasize that the T1: it doesn't include insecticides. Which consists of 60 gorgojos and 120 gr of rice in each treatment, the evaluation is carried out quincenalmente at the 24 hours after having installed the insecticides and he/she is renewed the gorgojos every 15 days and it is evaluated the different treatments of the gorgojos sitophillus spp in stored rice, detecting differs significant in each treatment due to the toxicity of the insecticide.